Suhu dan Waktu Inkubasi untuk Optimasi Kandungan Eksopolisakarida dan Fitohormon Inokulan Cair Azotobacter sp. LKM6 - Hindersah, Reginawanti; Sudirja, Rija (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Azotobacter inoculation could play an important role to enhance the effectiveness of bioremediation since bacterialexopolysachharides form a complex with heavy metal. So that metal mobility in soil and its uptake by plantsincreased. Azotobacter also produce phytohormone which induce roots growth and subsequently the uptake ofnutrients. The objective of this research was to obtain optimal incubation temperature and time in Azotobacter sp.LKM6 liquid inoculants production in the fermentor to maximize the synthesis of exopolysachharides andphytohormones. The experiment arranged in Completely Randomized Design consisted of two incubationtemperature (room temperature and 300C). At 24, 36, and 48 hours incubation, the concentration of EPS andphytohormone cytokinin and giberrelin were occurred. The experimental results were 1) the best temperature andincubation time to produce Azotobacter sp. LKM6 liquid for bioremediation of heavy metal-contaminated soil was30oC and 48 hours, and 2) inoculants production at 300C for 48 jam produce liquid inoculants containing 2.87mg L-1 exopolysachharides, 81.0 mg L-1 cytokinins and 18.7 mg L-1 giberrelin, and 13.12 x 108 cell ml-1.